Pengaruh Current Ratio (CR) dan Return on Assets (ROA) terhadap Nilai Perusahaan pada Perusahaan Manufaktur Sub Sektor Aneka Industri di Bursa Efek Indonesia (BEI) Periode 2015 – 2024 - Alvina Ghalda; Tri Sulistyani (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
The assessment of a company's value is crucial for investors to identify its prospects and performance. Financial ratios such as the Current Ratio (CR) and Return on Assets (ROA) are used to analyze factors affecting the company's value. This study aims to analyze the impact of CR and ROA on company value in manufacturing companies within the Miscellaneous Industries sub-sector for the period 2015–2024. The study uses a quantitative approach with data from annual financial reports of companies listed on the Indonesia Stock Exchange. Data analysis is conducted using panel data regression with the Random Effect Model (REM) as the best model. The dependent variable is company value, measured by Price to Book Value (PBV), while the independent variables consist of CR and ROA. The results show that CR does not have a significant effect on company value, while ROA significantly affects company value. Simultaneously, CR and ROA are proven to significantly affect company value, indicating that the combination of liquidity and profitability plays an important role in explaining PBV variations. This finding suggests that investors pay more attention to profitability than liquidity in the Miscellaneous Industries sector.